De melancólicos a rumberos… de los Andes a la Costa. La identidad colombiana y la música caribeña (2009)
ABSTRACT: The process of construction, profiling and management of national identities has been a cornerstone in the configuration and perpetration of nation-states. The following article offers an analysis in this direction, focusing on the role that music has played in establishing a colombianidad (colombianness) that is functional for the state and its hegemonic groups.